Biochemical Characterization of a Recombinant TRIM5α Protein That Restricts Human Immunodeficiency Virus Type 1 Replication - Langelier, Charles R. (American Society for Microbiology (ASM), 2008)
The rhesus monkey intrinsic immunity factor TRIM5α(rh) recognizes incoming capsids from a variety of retroviruses, including human immunodeficiency virus type 1 (HIV-1) and equine infectious anemia virus (EIAV), and inhibits the accumulation of viral reverse transcripts. However, direct interactions between restricting TRIM5α proteins and retroviral capsids have not previously been demonstrated using pure recombinant proteins. To facilitate structural and mechanistic studies of retroviral restriction, we have developed methods for expressing and purifying an active chimeric TRIM5α(rh) protein containing the RING domain from the related human TRIM21 protein. This recombinant TRIM5-21R protein was expressed in SF-21 insect cells and purified through three chromatographic steps. Two distinct TRIM5-21R species were purified and shown to correspond to monomers and dimers, as analyzed by analytical ultracentrifugation. Chemically cross-linked recombinant TRIM5-21R dimers and mammalian-expressed TRIM5-21R and TRIM5α proteins exhibited similar sodium dodecyl sulfate-polyacrylamide gel electrophoresis mobilities, indicating that mammalian TRIM5α proteins are predominantly dimeric. Purified TRIM5-21R had ubiquitin ligase activity and could autoubquitylate with different E2 ubiquitin conjugating enzymes in vitro. TRIM5-21R bound directly to synthetic capsids composed of recombinant HIV-1 CA-NC proteins and to authentic EIAV core particles. HIV-1 CA-NC assemblies bound dimeric TRIM5-21R better than either monomeric TRIM5-21R or TRIM5-21R constructs that lacked the SPRY domain or its V1 loop. Thus, our studies indicate that TRIM5α proteins are dimeric ubiquitin E3 ligases that recognize retroviral capsids through direct interactions mediated by the SPRY domain and demonstrate that these activities can be recapitulated in vitro using pure recombinant proteins.